Ciągłość kompozycji florystycznej pomiędzy dwoma zbiorowiskami roślinnymi – Carici elongatae-Alnetum oraz Fraxino-Alnetum - Czapiewska, Natalia; Dyderski, Marcin; Jagodziński, Andrzej; Paź, Sonia (Leśne Prace Badawcze, 2017)
One of the crucial debates in vegetation ecology is whether plant communities are discontinuous, distinguishable units or whether they change continuously. Phytosociology assumes discontinuity and its methodology requires subjective sampling during vegetation inventories. For that reason, some researchers argue that phytosociology artificially creates discontinuity among plant communities. Our aim was to assess the continuity between ash-alder riparian forest ( Fraxino-Alnetum ), and alder swamp forest ( Carici elongatae-Alnetum ), and to check whether discontinuity observed between these two plant associations is an effect of subjective sample plot choice. We conducted 57 phytosociological relevés within a regular grid covering potential sites of both plant communities. All relevés were arranged in order of decreasing relative cover of the diagnostic species for each plant association resulting in a gentle gradient, indicating a continuous transition from Fraxino-Alnetum to Carici elongatae-Alnetum . Similar results were obtained by detrended correspondence analysis. The proportion of species from the Querco-Fagetea class, typical to Fraxino-Alnetum , was decreasing with increasing proportion of species from the Alnetea glutinosae class, typical to Carici elongatae-Alnetum . This shift followed a gradient of ecological light-moisture indicator values. Our results confirmed continuous transition between two plant communities and led us to the conclusion that discontinuity resulted from the standard sampling protocol used in classical phytosociology. This protocol, however, is useful in searching for typological patterns, required for classification of plant communities, which is the main aim of phytosociology. Nevertheless, it does not provide full insight into the variability of vegetation and introduces uncertainty when trying to understand ecosystem dynamics. This uncertainty should be taken into account when phytosociological data are used for nature conservation recommendations and to draw conclusion about vegetation dynamics.